Powiązania niemieckiego systemu wspólnego oszczędzania na cele mieszkaniowe z globalnym popytem - Nowak, Andrzej (Wydział Prawa i Administracji UAM, 1997)
The author gives an analysis of relations between housing industry and other branches of the economy. He demonstrates that State interference aimed at increasing the building demand contributes to a growth of voluntary savings. Functional principles of German corresponding system are presented with special stress of the fact that some balance between savings and investments is a very important advantage of the whole system what assumes stability to the conjuncture of the whole of economy. The author notes that in a situation where the number of participants to the system diminishes expressively - the credit amounts accorded to the others are not much lower. The bigger is the part of common savings for housing purposes in the financing of the economy, the less State interference and help is needed.
Connections between German system of common savings for housing purposes and aggregated demand